Homing behaviour of Atlantic salmon (Salmo salar) during final phase of marine migration and river entry - Davidsen, Jan Grimsrud; Rikardsen, Audun H.; Thorstad, Eva Bonsak; Halttunen, Elina; Mitamura, Hiromichi; Præbel, Kim; Skardhamar, Jofrid; Næsje, Tor (Canadian Journal of Fisheries and Aquatic Sciences, 2013)
Little is known about Atlantic salmon behaviour during the last phase of the marine homing migration and subsequent river entry. In this study, 56 adult Atlantic salmon in the Alta Fjord in northern Norway were equipped with acoustic transmitters. Salmon generally followed the coastline, but their horizontal distribution was also affected by wind-induced spreading of river water across the fjord. Mean swimming depth was shallow (2.5–0.5 m), but with dives down to 30 m depth. Timing of river entry was not affected by river flow, diel periodicity, or tidal cycles. Movements during the last part of the marine migration and river entry were unidirectional and relatively fast (mean 9.7 km·day−1). However, migratory speed slowed as salmon approached the estuary, with a significantly lower speed in the innermost part of the estuary than in the open fjord. Migration behaviour seemed not to be affected by handling and tagging, as there were no behavioural differences between newly tagged fish and those captured and tagged 1 year before their homing migration.